A self-powered multi-functional sensor based on triboelectric nanogenerator for monitoring states of rotating motion. (May 2021) - Lin, Senpeng; Zhu, Lifeng; Qiu, Ye; Jiang, Zhengyang; Wang, Yifei; Zhu, Jun; Wu, Huaping
Abstract: The promptly growing technique of powerless devices based on triboelectric nanogenerator (TENG) offers an opportunity to get rid of external power sources. Especially, plenty of self-powered rotating sensors are proposed but short of the capability to simultaneously detect multi-rotating parameters. A self-powered states of rotating motion sensor (SRM-Sensor) is developed for synchronously monitoring rotating displacement, speed, acceleration. It is mainly constructed by rack-shaped plates and incomplete gears. Symmetrical setup of incomplete gears design amplifies triboelectric output signal twofold and the sensitivity is 580 mV/rpm. After connecting to rectified bridge and filter capacitor circuit, the output voltage shows an intuitionistic relationship with rotating speed. The calculated integral and derivation of output voltage curve perfectly fit the rotating displacement and acceleration. The proposed SRM- Sensor potentially paves the way for a rotating motion sensing system with self-powered characteristics to the fields of industrial revolve detecting. Graphical Abstract: ga1 Highlights: A self-powered multi-functional sensor that is based on the triboelectric nanogenerator. Rectified bridge and filter capacitor change output voltage to effective value. Symmetrical uncompleted gears design modify input rotating speed twice and enhance output voltage. Effective value, integration, differentiation correspond to rotating speed, displacement, acceleration.